Iridium-catalyzed 1, 5-(aryl)aminomethylation of 1, 3-enynes by alkenyl-to-allyl 1, 4-iridium(i) migration. Issue 6 (21st December 2018) - Ruscoe, Rebecca E.; Callingham, Michael; Baker, Joshua A.; Korkis, Stamatis E.; Lam, Hon Wai
Abstract : A novel multicomponent coupling reaction involving the iridium-catalyzed 1, 5-difunctionalization of 1, 3-enynes with arylboronic acids and triazinanes is described. Abstract : A novel multicomponent coupling reaction involving the iridium-catalyzed 1, 5-difunctionalization of 1, 3-enynes with arylboronic acids and triazinanes is described. A key step in this 1, 5-(aryl)aminomethylation reaction is the alkenyl-to-allyl 1, 4-iridium(i ) migration.